The role of surface defects in the adsorption and sesorption of hydrogen on Ni(111) - Rendulic, K.D.; Winkler, A.; Steinrück, Hans-Peter (Surface Science, 1987)
On a smooth Ni(111) surface both the β and the β state show activated adsorption. The desorption flux is highly peaked towards the surface normal. Defects introduce non-activated adsorption sites which lower the desorption temperatures in flash desorption. At the same time a cosine dependence of the desorption flux is obtained. Because of its small sticking coefficient the β state is already influenced by small defect concentrations; the β state is only affected on highly defective surfaces. © 1987 Elsevier Science Publishers B.V.